Uji Cemaran Mikroba Pada Kosmetik Pelembab Wajah yang Beredar di Toko Kosmetik Kelurahan 17 Ilir Kecamatan Ilir Timur I Palembang - Ririn Wayan Pratama; Dani Prasetyo (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Microbial contamination test of facial moisturizer products sold at beauty stores in 17 Ilir has been issued. The aim of this study is to examine whether the facial moisturizers hit microbial limits as determined by the Food and Drug Supervisory Institution (Badan Pengawas Obat dan Makanan â€“ BPOM) which is 103Â colonies/g or colonies/ml, using the Total Plate Number (ALT) method. The results of the test reckon that 5 facial moisturizer samples before applicated have already met BPOM requirements in a range from ALT values of 0 colonies/ml to860 colonies/ml. Somehow, the same products become underqualified with ALT additional values of 1,7104colonies/ml up to 1,01106 colonies/ml after getting used.